Can a pathological model improve the abilities of the paretic hand in hemiplegic children? The PAM-AOT study protocol of a randomised controlled trial. Issue 12 (30th December 2021) - Verzelloni, Jessica; Errante, Antonino; Beccani, Laura; Filippi, Mariacristina; Bressi, Barbara; Cavuto, Silvio; Ziccarelli, Settimio; Bozzetti, Francesca; Costi, Stefania; Pineschi, Elena; Fogassi, Leonardo; Ferrari, Adriano
Abstract : Introduction: Action Observation Treatment (AOT) is an innovative therapeutic approach consisting in the observation of actions followed by subsequent repetition. In children with unilateral cerebral palsy (UCP), it improves upper limb function in daily activities. The standard paradigm of AOT requires the observation of healthy models; however, it has been demonstrated that the mirror neuron system of children with UCP is more activated by observation of pathological models, showing a similar motor repertoire, than by the healthy model, suggesting that AOT based on pathological models is superior to the standard paradigm of AOT in the functional rehabilitation of the affected upper limb of children with UCP. Methods and analysis: This protocol describes an active two-arm randomised controlled evaluator-blinded trial. Twenty-six children with UCP will participate in 3 weeks of intensive AOT: the experimental group will observe a pathological model, while the control group will observe a typically developed model. The primary outcome is the spontaneous use of the paretic hand, measured with the Assisting Hand Assessment. Secondary outcome measures are the Melbourne Assessment of Unilateral Upper Limb Function, the ABILHAND-Kids and the Activities Scale for Kids-performance. Assessments will be performed at baseline (T0), at the end of intensive AOT (T1), at 8–12 weeks (T2) and at 24–28 weeks (T3) after the end of intensive AOT. Ethics and dissemination: The trial was approved by the Area Vasta Emilia Nord Ethics Committee (AVEN prot. n. 133117, 29 November 2018), and it was prospectively registered on ClinicalTrials.gov. The results will be submitted for publication to a peer-reviewed journal, discussed with parents of children participating in the trial and disseminated at suitable conferences. Trial registration number: NCT04088994 ; Pre-results.